COMPARISON OF PHYSICAL FITNESS LEVEL OF DAY AND BOARDING SCHOOL STUDENTS IN OFFA, OFFA L.G.A. - Surajudeen Tosho (Program Pascasarjana Universitas Negeri Jakarta, 2021)
Health is a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity. The study compared the physical characteristics and fitness levels of day and boarding students in Offa Local Government Area, Kwara State. The population for this study comprised 210 students in day and boarding schools in Offa LGA. Systematic sampling technique was used to select 20 students each from day and boarding school. Ex-post facto research design was adopted for the study, Standardized instrument (stadiometer, body fat/hydration monitoring scale, measuring non-elastic tape, stop watch, whistle, floor mat, sit and reach box) were used for the study. Split half method was used to ascertain the reliability of the instrument and a correlation coefficient of 0.63r was obtained. Descriptive statistics of mean and standard deviation and inferential statistic of t-test were used to analyse the data . It findings revealed that boarding students were taller than the day students while both groups were physically fit and healthy. Furthermore, day and boarding students were significantly different in their cardio-respiratory endurance while both were not significantly different in muscular strength and body flexibility. It was therefore recommended that there should be a regular physical fitness assessment and screening consideration for students in day and boarding schools for early detection of any deviation from normalcy to take immediate corrective action while the school should organise physical fitness programme for all students on regular basis to develop their cardio respiratory endurance, muscular strength and body flexibility. Key Words: Muscular, Strength, Flexibility, Fitness